LANGUAGE STYLE IN KING’S SPEECH MOVIE - Emilya Somia; Meisuri Meisuri (State University of Medan, 2012)
Abstract One aim of this article is to show through a concrete example how language style used in movie. The illustrative example is taken from the dialogue of King’s Speech movie. Central to the analysis proper form of dialogue in King’s Speech movie that contain of language style; i.e. frozen, formal, consultative, casual, and intimate. 339 dialogue were interpreted by actor, and it was found that the use of language style. Keywords: movie; language style